Filip Buonaccorsi Kallimach „De legitimo amore” - Głombiowska, Zofia (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The article is an analysis of three works by Filip Kallimach (Filippo Buonaccorsi) regarding marriage (elegy XXII, Epithalamium Fanniae ac Musaei, carmen Ad se ipsum). In the collections of Roman elegies from the Augustian era, there are no wedding pieces. The source of Callimachus’ idea is found by the author of the article in Epithalamium in Stellam et Violentillam by P. Papinius Statius and, indirectly, through the epithalamium of Statius – in the unpreserved elegies of L. Arruntius Stella, a poet of Domitian times.